THE IMPORTANCE OF HUMAN FACTOR IN ORGANIZATIONS - Laureano , Rafael Ramos; Reis Filho , Ramilio Ramalho (Revista Interface Tecnológica, 2020)
When talking about the human factor, we face a concept that treats individuals as tools in the job market. The purpose of this article is to demonstrate that the person who feels satisfied in the work environment becomes a determining factor for the company’s competitiveness, in addition to mentioning the importance of people management, as it works with methods, skills, policies and well-defined techniques, so that the individual can plan, organize, manage, direct and control the processes within an organization. The methodologies used in this work were bibliographic and exploratory in order to prove the importance of the theme and to allow for a more in-depth analysis of the study theme. With the results of the research, the need to change the behavior of companies towards their employees is demonstrated, ceasing to treat them as work tools and easy to replace, starting to understand them as human beings who have emotions, feelings and personal goals, and as a factor of competitiveness and an ally in the search for the organization’s success.